PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DALAM MENINGKATKAN PRODUKTIVITAS KERJA PADA PEKERJA INDUSTRI: LITERATURE REVIEW - Annissa Nuraini, (2020)
The implementation of occupational safety and health programs is one of the maintenance provided by the company to workers. The application is significant to create safety system, unity of work by providing sense of security, comfort, and peace increase workers productivities. The purpose of this study determine the relationship between application of occupational safety and health improve the industrial workers productivities. This research uses the literature review method. The results of the study show there were 20 studies from 2010 to 2020. Most of the research designs used descriptive analysis in a quantitative approach. Based on journal analysis there was a relationship between the application of occupational safety and health improve workers productivities. This research concludes that application of occupational safety and health in industrial companies had implemented standards and policies so that production results can be achieved and productivity increased. Proven the higher application of occupational safety and health, the work productivity will increase to produce a quality product and the production targets can be achieved. This research suggests that the company should maintain the implementation of occupational safety and health, if possible it can be improved by conducting supervision and enforcement by regulations to be obeyed by workers.